2014
DOI: 10.1002/tox.22087
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of combined fluoroquinolone and tetracycline exposure in zebrafish (Danio rerio)

Abstract: Fluoroquinolones (FQs) and tetracyclines (TCs), the two b-diketone antibiotics (DKAs), are two frequently detected pollutants in the environment; however, little data are available on their combined toxicity to zebrafish (Danio rerio). This study reports that toxicologic effects of combined DKA (FQs-TCs) exposure on zebrafish were comparable with or slightly less than those of TCs alone, showing that TCs played a major toxicologic role in the mixtures. The effects of FQs, TCs, and DKAs on malformation rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 62 publications
1
49
0
2
Order By: Relevance
“…2). The previously behavioral study by our group revealed that DKAs reduced the swimming activity and induced equilibrium loss in larvae (Zhang et al, 2016). Another sensitive endpoint was the abnormal yolk sac resorption in conjunction with prominent oedemas.…”
Section: Discussionmentioning
confidence: 90%
“…2). The previously behavioral study by our group revealed that DKAs reduced the swimming activity and induced equilibrium loss in larvae (Zhang et al, 2016). Another sensitive endpoint was the abnormal yolk sac resorption in conjunction with prominent oedemas.…”
Section: Discussionmentioning
confidence: 90%
“…Water was dechlorinated and filtered by reverse osmosis (pH 6.5–7.5), and Instant Ocean band of salt was added to raise the specific conductivity to 450–1000 μS/cm. Zebrafish were fed twice daily with live Artemia (Jiahong Feed Co., Tianjin, China) and dry flake diet (Zeigler, Aquatic Habitats, Apopka FL, USA) [ 10 ]. The fertilized and normal embryos were inspected and staged for subsequent experiments under a stereomicroscope according to Kimmel and coworker’s method [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have primarily focused on the toxicity of single DKA species to explore the relevant toxicological mechanisms. However, in real-world aquatic environments, mixtures of several different DKA species may have entirely different toxicological mechanisms, which can lead to complex, combined toxicity actions by DKAs mixtures [ 9 10 ]. For in vivo experiments, changes in metabolic transformation and distribution of DKAs make the toxicological research more complicated [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of zebrafish embryo's tail coiling was counted within 1 min period. Cardiac toxicity was evaluated by measuring heart rates of zebrafish embryos in natural lateral recumbent position within 1 min period without anesthesia to avoid bias heartbeat scoring [73,74]. Zebrafish larvae were not fed during the experiment.…”
Section: Zebrafish Toxicity Assay Of Fla and Flbmentioning
confidence: 99%